2024
DOI: 10.3389/fresc.2023.1336514
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of public transport use among people with disabilities: a scoping review

C. R. Mwaka,
K. L. Best,
C. Cunningham
et al.

Abstract: Barriers to public transport use may be experienced differently by people with various types of disabilities (e.g., physical, intellectual, cognitive, sensory). Thus, it is important to identify the variable needs within each element of the travel chain. For example, the unavailability or low volume of auditory announcements in a stop or station or on the public transport vehicle may be a barrier to people with visual disability who rely on hearing the information. Consequently, this could provoke negative emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In terms of social networks, as highlighted in recent literature reviews [13,44], transportation staff, particularly drivers, have been identified as potential supporters or hindrances to the use of transportation for PWDs in commuting to work. In our study, transport providers emphasized their responsibility to adequately train drivers, to ensure inclusive behaviors toward PWDs.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of social networks, as highlighted in recent literature reviews [13,44], transportation staff, particularly drivers, have been identified as potential supporters or hindrances to the use of transportation for PWDs in commuting to work. In our study, transport providers emphasized their responsibility to adequately train drivers, to ensure inclusive behaviors toward PWDs.…”
Section: Discussionmentioning
confidence: 99%